Application and mechanism of percutaneous puncture disc platelet-rich plasma injection for lumbar disc herniation: a systematic review and meta-analysis - Xingyang Xie; Yalin Peng; Guoping Liu; Qi Cao (Journal of Orthopaedic Surgery and Research)
Abstract Background Although platelet-rich plasma (PRP) has been increasingly used for the treatment of lumbar disc herniation (LDH), its effect on patient outcomes lacks systematic assessment. This study aimed to compare the effects of PRP treatment and other treatments in LDH patients using the Oswestry Disability Index (ODI) and two visual analog scales (VASs) via a meta-analysis. Methods We systematically searched relevant studies from the PubMed, Embase, and Cochrane Library databases from their inception to October 24, 2024. The visual analog scale of back pain (VAS-BP), visual analog scale of leg pain (VAS-LP), pooled VAS and ODI score data at 1, 3, 6, and 12 months after surgery were extracted. A fixed/random effects model was used for the meta-analysis. Sensitivity analysis was performed to explore the main sources of heterogeneity and investigate the robustness of the results. Results This meta-analysis included 8 studies involving 697 patients. The results revealed that the ODI in the PRP group was significantly lower than that in the control group at most time points after surgery (P < 0.05). The VAS-BP score at 3 and 6 months after surgery, the VAS-LP score at 3, 6, and 12 months after surgery, and the pooled VAS score at the 3 months after surgery (P < 0.05) were significantly lower in the PRP group. Conclusions Intradiscal PRP injection can significantly alleviate long-term pain and dysfunction in LDH patients, and its efficacy is greater than that of the control treatment; however, further studies are needed to verify the long-term mechanism involved.